Anthropometric measures associated with incarceration length of persons deprived of their liberty. - Baccon, Wanessa Cristina; Salci, Maria Aparecida; Oliveira, Rosana Rosseto de; Previdelli, Isolde Terezinha Santos; Rêgo, Anderson da Silva; Sanches, Rafaely de Cassia Nogueira; Moraes, Talita Evelin Nabarrete Tristão de; Marques, Priscila Garcia (Acta Paulista de Enfermagem, 2023)
Objective: To analyze the anthropometric measures associated with incarceration length of people deprived of their liberty. Methods: This is a cross-sectional study carried out with 220 men deprived of their liberty. Data were collected using an instrument that included information on current incarceration, sociodemographic information and living conditions before incarceration, in addition to measuring anthropometric measures. Descriptive statistics, association tests and adjustment of binary logistic regression models controlled by incarceration length (up to 1 year and more than 1 year) were used. Results: There was a significant association between incarceration length and abdominal circumference (OR 0.41; 95%CI 0.16-0.97). The results of Spearman's correlation showed that, as the incarceration length increased, the anthropometric measures decreased, with a negative relationship of weak magnitude and significant only for the conicity index (r=-0.1648; p=0.0144). Adjusted models controlled for incarceration length showed significant associations with age in years (OR 1.08; 95%CI=1.04;1.12) and abdominal circumference; age (OR 1.08; 95%CI 1.04-1.12) and waist-to-height ratio; and age (OR 1.10; 95%CI 1.06-1.14), years of education (OR 2.17; 95%CI 1.10-4.26) and having a partner (OR 0.46; 95%CI0.22-0.93) with the conicity index. Conclusion: As incarceration length increases, there is a reduction in the anthropometric measures of persons deprived of their liberty. Anthropometric variables directly influence the development of non-communicable chronic diseases and must be monitored to develop strategies that minimize the risks and health problems of this vulnerable population.